A spotlight of amendments in the Jordanian Arbitration Law in 2018 - Al-Braizat, Hamza Madallah; Jiang, Zuoli (Journal of Economic, Administrative and Legal Sciences, 2019)
Jordan has witnessed rapid development in its trade relations after its accession to the World Trade Organization and the signing of many agreements accompanied by rapid economic development. This led to the amendment of the Arbitration Act in 2001.The amended law introduces new and anticipated changes to the procedural framework for arbitration in Jordan, many of which can be traced to the UNCITRAL Model Law as amended in 2006.The old law was amended in 2001, prior to the recent amendment to the UNCITRAL Model Law.In addition, the amended law provides for much-needed clarity on some of the ambiguities of the former regime.The new law is based on the 2006 UNCITRAL Model Law and is therefore considered to be the closest to the Model Law, although it contains some amendments to its provisions, in order to comply with Jordanian legislation. we intended to address the entire law. However, since it is impossible to cover this accurately ("Amended Law"). Because of the limited space, we have to write, we will, therefore, cover the main points and compare them with the Model Law.The amended law shall enter into force thirty (30) days after its publication in Official Gazette No. 5513/2018 dated 2 May 2018. The amended law shall apply to arbitration in Jordan, as well as arbitration agreed by the parties to subject such arbitration proceedings to the amended law. On the nature of the legal relationship that arouses the dispute.Explanation of the substantive amendments that have been made including the scope of application of the new law and the added definitions and interpretations 'Procedures for the formation of the arbitral tribunal' Notification of the parties to the dispute 'Arbitration agreement' Challenges of the arbitrators and their isolation 'Representation of the parties' Articles 51 and 52 and the amendment to the Constitutional Court's decision to distinguish Sadr's decision from the Court of Appeal as a competent court in the previous law.
Keywords: Jordanian Arbitration Law; the most important amendments; UNCITRAL Model Law